Pengaruh Konsentrasi Gula Terhadap Karakteristik Fisika, Kimia dan Aktivitas Antioksidan Teh Kombucha Daun Belimbing Wuluh (Avverhoa bilimbi Linn.) - Fanny Fajrin Aulia Rosyada; Eva Agustina; Hanik Faizah (Universitas Trunojoyo Madura, 2023)
One of the fermented traditional drinks that can have a health effect is kombucha. The materials that can be used in making kombucha is wuluh starfruit leaves. The research was conducted to determine the effect of sugar concentration of the physical, chemical characteristic, and antioxidant activities of wuluh starfruit leaf kombucha tea. This research is an experimental study with a complete randomized design method (CRD) consisting of 3 treatments. Kombucha wuluh starfruit leaves are made with a sugar concentration of 10%, 15% and 20%. The physical characteristics tested include organoleptic tests and the chemical characteristics include a test of the pH value, the total levels of titrated acids (tat), phenolics statistically analyzed using the Kruskal Wallis test and the Mann Whitney test. The alcohol data and antioxidant activity (IC50) were analyzed descriptively. The results of the Kruskal Wallis test have a significant difference in the pH. The best result based on the physical, chemical characteristic and antioxidant activity is were kombucha with a sugar concentration of 10% with a pH value of 3, a tat content of 0.11%, a phenolic content of 87.33 mg/ml GAE, an alcohol content of 0.41% and an IC50 value of 3.65 ppm.